Screen time exposure and academic performance, anxiety, and behavioral problems among school children - Mohammad Sidiq; Balamurugan Janakiraman; Faizan Kashoo; Rayan Jastania; Abdullah Ibrahim Alhusayni; Abdullah Alzahrani; Aksh Chahal; Alagappan Thiyagarajan; Imran Khan; Chandan Kumar; Rajkumar Krishnan Vasanthi; Fahad Alanazi; et al. (PeerJ)
Background The growth of the digital landscape has surely outpaced research on the effects of screen media on the health, learning, and development of children. The potential risk-to-benefit ratio of screen media exposure for education and entertainment purposes warrants further exploration. Therefore, we aimed to investigate the relationships between screen time and academic performance, anxiety, and outdoor playing among school children in India. Methods A total of 537 parents responded to this online survey and reported approximately 537 Indian school children (mean age 10.9 years) from five schools. Data was collected using an e-questionnaire which consisted of a socio-demographic domain, recreational activities, self-reported physical measures, academic performance, information related to children’s screen time, the Spence Children Anxiety Scale (SCAS), and the Pediatric Symptom Checklist (parent version) instruments. We employed multivariate linear regression models to estimate the association between children’s screen time and the predictor variables with 0.05 alpha as level of significance. Results The mean screen time was 3.06 ± 1.22 h/day, the average duration of outdoor play per week was 11.23 ± 4.1 h, and the mean body mass index (BMI) was 18.2 ± 3.2. Screen time (h) in a typical week was positively correlated with BMI, the SCAS anxiety score, and behavioral problems and negatively correlated with academic performance. School children’s screen time was a predictor of their BMI, behavioral symptoms, and academic performance according to the linear regression analysis. Conclusion Our findings pointed out that screen time was associated with increased BMI, behavioral problems and poor academic performance. These insights shall be used for development of targeted tailored interventions and strategies to reduce childhood obesity related to screen time. Further research is necessary to rule out the influence of other intricate factors, such as sleep, parental practices, family connectedness, and supervision of parents. The careful use of digital media must serve as a positive force in children’s educational and developmental trajectories.